Evaluation of dental anxiety in children with Down's syndrome using dog-assisted therapy: A pilot study - Shilpa S Naik; Amil Joshi; J Jasmin Winnier; Diksha D Patil; Priya Jayant Gore; Sonal Sanjay Mali (Wolters Kluwer Medknow Publications, 2023)
Background: Dental anxiety and fear are the major treatment challenges faced by pediatric dentists. Oral hygiene in children with Down's syndrome is highly compromised in comparison to their healthy counterparts. Animal-assisted therapy, through dogs, has been beneficial in alleviating dental fear and anxiety in healthy pediatric population. Aim: The aim of the study was to assess the impact of dog-assisted therapy (DAT) on children with Down's syndrome undergoing dental examination and fluoride varnish application in dental operatory. Materials and Methods: Twenty children with Down's syndrome between 5 and 12 years of age were selected. Group A (intervention group): DAT was carried out in the dental operatory. Group B (control group): Dental treatment was performed in the absence of a therapy dog in the dental operatory. Anxiety levels were evaluated by recording the pulse rate and revised modified faces version of the Modified Child Dental Anxiety Scale (MCDAS[f]). Statistical Analysis: The intergroup comparison of pulse rate was done using an unpaired t-test, whereas the variation in intragroup pulse rate was analyzed using the Analysis of Variance test. The anxiety scores were subjected to a paired t-test for intragroup comparison with P < 0.05 considered to be statistically significant. Results: Reduction in dental anxiety was observed in the intervention group (P < 0.001). Conclusion: DAT can be used as an effective behavior management technique for children with Down's syndrome undergoing dental examination and simple dental procedures in the dental operatory.